Analisis Jaringan Komunikasi Interpersonal Kelompok Tani dalam Koordinasi Penggunaan Combine Harvester di Pidoli Lombang - Rony Rahmat Hidayat Hasibuan; Utari Azrani; Putra Kurniawan (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
This study examines the interpersonal communication network of farmer groups in coordinating the use of combine harvesters for rice harvesting in Pidoli Lombang Village Panyabungan Subdistrict Mandailing Natal Regency. The research focuses on two farmer groups Willem Iskander and Biara Dagang with a total of 60 farmer respondents. The study applies a descriptive quantitative approach using Social Network Analysis SNA. Primary data were collected through a survey and sociometric questions to construct an actor to actor communication matrix then analyzed using UCINET VI and visualized with NetDraw. The analysis focuses on outdegree indegree closeness and betweenness centrality to identify key actors and information flow patterns related to harvest scheduling field rotation cost agreement and operator assignment. The results show that in the Willem Iskander farmer group actor NS holds the most strategic position as an information disseminator a main reference and a communication broker as indicated by outdegree 0.207 indegree 0.62 closeness 1.97 and betweenness 8.72. In the Biara Dagang farmer group dissemination and brokerage roles are more distributed across several members with the highest outdegree for PL 0.76 the main reference for PN 0.62 the highest closeness for AK 1.95 and a prominent brokerage role for KH 3.27. In conclusion the communication network structure in Pidoli Lombang forms central actors who shape the speed and direction of coordination in combine harvester use so strengthening the capacity of key actors may improve the effectiveness of harvest mechanization at the local level.